(untitled) (International Journal of Engineering and Computer Science, 2024)
This paper outlines the guidelines and requirements for students undertaking a computing project as part of their academic program. The project is a critical component of most undergraduate programs and is designed to provide students with the opportunity to apply theoretical knowledge to practical scenarios, demonstrating their ability to plan, execute, and present a complex piece of work. Unfortunately, there is currently a lack of clear and helpful guidance on how to conduct elementary research at this level, differentiate a computing project from other types of projects, and report it effectively. This paper aims to assist both computing students and faculty in carrying out and reporting on final-year research projects. It documents the differences in research approaches across various computing disciplines and provides a guiding framework for faculty overseeing the undergraduate research process. The guidelines cover various aspects of the project process, including the development of a project proposal, conducting the research, and writing the final report. It emphasizes the importance of early planning, regular supervision, and adherence to academic standards, particularly in the presentation and documentation of the project work. Additionally, the document details the criteria for project assessment, highlighting the need for clarity, innovation, and rigor in both the practical and written components of the project. Instructions on the submission process and the responsibilities of students and supervisors throughout the project lifecycle are also included.